The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1192/bjp.176.5.479
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in the use of the Mental Health Act 1983 in England, 1984–1996

Abstract: Formal admissions are more common than they were in 1984, despite there being fewer psychiatric beds. This is probably due to changes in the provision of psychiatric services, and changing societal pressures on psychiatrists away from libertarianism and towards coercion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 7 publications
2
32
0
1
Order By: Relevance
“…In the european and worldwide clinical trials, the prevalence of involuntary hospitalization ranges from 3.2% and 42% (Zinkler & Priebe 2002;Salize & Dressing 2004;Zhou et al 2015;Lastly, Rittmannsberger et al 2004) conducted a multicentre study involving twenty-four European countries and reported a prevalence of involuntary hospitalizations corresponding to 11.4%, evaluated in a single day. Prevalence and criteria of involuntary admissions change widely across different countries; some possible explanations refer to differences among legislature (Riecher-Rossler & Rossler 1993;Zinkler & Priebe 2002;Salize & Dressing 2004), organization of the mental health services (Lelliott & Audini 2003), culture and ethnicity (Riecher-Rossler & Rossler, 1993;, professional ethic (Zinkler & Priebe 2002;Zhou et al 2015) and social pressures on psychiatrists (Hotopf et al 2000). We found statistically significant differences in terms of socio-demographic and clinical features, comparing involuntary versus voluntary hospitalizations.…”
Section: Discussionmentioning
confidence: 68%
“…In the european and worldwide clinical trials, the prevalence of involuntary hospitalization ranges from 3.2% and 42% (Zinkler & Priebe 2002;Salize & Dressing 2004;Zhou et al 2015;Lastly, Rittmannsberger et al 2004) conducted a multicentre study involving twenty-four European countries and reported a prevalence of involuntary hospitalizations corresponding to 11.4%, evaluated in a single day. Prevalence and criteria of involuntary admissions change widely across different countries; some possible explanations refer to differences among legislature (Riecher-Rossler & Rossler 1993;Zinkler & Priebe 2002;Salize & Dressing 2004), organization of the mental health services (Lelliott & Audini 2003), culture and ethnicity (Riecher-Rossler & Rossler, 1993;, professional ethic (Zinkler & Priebe 2002;Zhou et al 2015) and social pressures on psychiatrists (Hotopf et al 2000). We found statistically significant differences in terms of socio-demographic and clinical features, comparing involuntary versus voluntary hospitalizations.…”
Section: Discussionmentioning
confidence: 68%
“…112 Even when clinicians' judgements are consistent with the law, unexplained variations in decision-making exist, influenced by factors such as clinician characteristics, local service provision, community support for patients, patient ethnicity, age and education and attitudes to mental health. 111,[113][114][115] Although the exact reasons for increasing detention rates have not been delineated, our findings suggest one possibility: the increasing risk aversion in clinical practice. Clinicians in our study highlighted how risk assessment and management is increasingly the focus of their concern in MHA assessments.…”
Section: Discussionmentioning
confidence: 75%
“…In 1996, over 26 000 people in England with mental disorders were deprived of their liberty and detained in hospital without their consent under the Mental Health Act 1983 (Hotopf et al, 2000). Despite the rapidly increasing use of existing legislation, there has been little research into the operation of the Act and the various measures it incorporates, to ensure against unjustified detention in hospital (Wall et al, 1999).…”
Section: Discussionmentioning
confidence: 99%